Towards an understanding of the children’s responses to traumatic stress following A natural disaster-The 2004 Tsunami - Dissanayake, G.R.K. (My University, 2005)
Natural disasters greatly affect the mental health of children. Not everyone, however, is equally affected by the stress of experiencing such an event. The present study examined the emotional impact of the 2004 tsunami on children, their efforts to cope and considered both risk and protective factors. This study included a stratified random sample of 126 nine to twelve year old school children (63 girls and 63 boys). The present study used an integrative conceptual model which includedthe examination of the relationships between the factors: level of exposure, aspects of the recovery environment, pre-existing child characteristics, emotional distress and coping. Both qualitative and quantitative methods were used for data collection and analysis. This study consisted of two phases of data collection. In the first phase, one hundred and twenty six children were assessed via researcher-developed two self-report survey instruments on emotional distress and coping, 15 months after the tsunami. Subsequently, in the second phase, twenty children were selected and interviewed to gain an in-depth understanding of their post-traumatic stress reactions 18 months after the tsunami. The data collection methods used in this study adhered to strict ethical standards.Pearson's coefficient of correlation, ANOVA, t-test, and multiple regression were employedto analyse the quantitative data. Qualitative interview data were analysed using the template analysis. The findings of the current study clearly demonstrate the effect natural disasters have on children and offer insights into how children attempt to cope with such experiences. The majority of children in the current study were experiencing mild to moderate levels of emotional distress.The level of emotional distress varied significantly depending upon the type of coping strategyused. Children's coping choices indicated that at various stages of a child's emotional experienceto a traumatic event, different methods of coping bring effective benefits. Children who had multiple exposures to traumatic events appear to be greater at risk of developing emotional distressfollowing the tsunami. Multiple regression analyses indicated that the risk/protective variables accounted for 44% of the variance in the level of emotional distress. Gender differences in experiencingstress reactions were also observed. Most tsunami-affected children, despite their stressors, indicated an ability to feel positive emotions and a sense of hope for the future. The findingsindicate tremendous resilience in the majority of children to cope with extreme distress. However,there is a small minority of children who continue to suffer from long lasting traumatic stressreactions; hence are at risk of developing psychological problems. Findings are discussed in light of the existing literature, focusing on possible and appropriate interventions in the aftermath of natural disasters. Limitations to the study, suggestions, and directions for future studies are also discussed